2020
DOI: 10.1097/scs.0000000000007284
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Smell and Taste Disorders in COVID-19: A Cross-sectional Study

Abstract: features of IPEH on histopathology include papillary structures and hyperplastic endothelial cells contained within the vascular lumen. It has been described in association with a wide range of lesions such as cavernous hemangiomas, varices, and lymphangiomas. Intravascular papillary endothelial hyperplasia can mimic angiosarcoma, a highly malignant tumor capable of metastasis. The distinction can be made on histopathology, with angiosarcomas showing tissue invasion beyond blood vessels and exhibiting malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…The remaining 18 studies were conducted in other regions (a pie chart showing distribution is included in the supplementary data provided— S1 Fig ). 10 studies were conducted in Asia: Turkey (n = 5) [ 18 , 27 , 38 , 41 , 50 ], Iran (n = 2) [ 22 , 55 ], India (n = 2) [ 33 , 52 ], Israel (n = 1) [ 32 ]. Four studies were conducted in North America: United States (n = 4), [ 21 , 42 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 18 studies were conducted in other regions (a pie chart showing distribution is included in the supplementary data provided— S1 Fig ). 10 studies were conducted in Asia: Turkey (n = 5) [ 18 , 27 , 38 , 41 , 50 ], Iran (n = 2) [ 22 , 55 ], India (n = 2) [ 33 , 52 ], Israel (n = 1) [ 32 ]. Four studies were conducted in North America: United States (n = 4), [ 21 , 42 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in Africa: Egypt (n = 2) [ 34 , 49 ], and two in South America: Brazil (n = 1) [ 53 ], Chile (n = 1) [ 15 , 53 ]. Of the 44 studies, twenty-five (56.8%) reported no funding requirements for the project [ 16 , 18 , 19 , 22 , 27 30 , 32 , 33 , 39 , 40 , 42 47 , 49 51 , 53 , 58 ]; six (13.6%) studies reported funding for the project (sources included academic institutions, government and not-for-profit organizations) [ 15 , 24 , 25 , 31 , 48 , 57 ], and thirteen (29.5%) did not report whether funding was provided [ 17 , 21 , 23 , 26 , 37 , 38 , 52 , 54 56 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 241 were included in the present systematic review and meta-analysis (Gamper et al, 2012; Liu et al, 2016; Adamczyk et al, 2020; Adedeji et al, 2020; Adorni et al, 2020; Aggarwal et al, 2020; Al-Ani and Acharya, 2020; Altin et al, 2020; Andrews et al, 2020; Anna et al, 2020; Asai et al, 2020; Bastiani et al, 2020; Beltran-Corbellini et al, 2020; Bergquist et al, 2020; Biadsee et al, 2020; Bidkar et al, 2020b; Boscolo-Rizzo et al, 2020a, 2020b, 2020c, 2021; Boudjema et al, 2020; Brandao Neto et al, 2020; Bulgurcu et al, 2020; Calica Utku et al, 2020; Carignan et al, 2020; Chary et al, 2020; Chen et al, 2020; Chiesa-Estomba et al, 2020; Cho et al, 2020; Chung et al, 2020; Cocco et al, 2020; Dawson et al, 2020; Dell’Era et al, 2020; De Maria et al, 2020; Durrani et al, 2020; Elimian et al, 2020; Farah Yusuf Mohamud et al, 2020; Fistera et al, 2020; Fontanet et al, 2020; Freni et al, 2020; Garg et al, 2020; Gelardi et al, 2020; Giacomelli et al, 2020; Gorzkowski et al, 2020; Gozen et al, 2020; GÜner et al, 2020; Gudbjartsson et al, 2020; Guillen Martinez et al, 2020; Haehner et al, 2020; Hintschich et al, 2020b; Horvath et al, 2020; Iversen et al, 2020; Izquierdo-Domínguez et al, 2020; Jain et al, 2020; Jalessi et al, 2020; Kacem et al, 2020; Karadas et al, 2020; Kempker et al, 2020; Kim et al, 2020; Klopfenstein et al, 2020; Konstantinidis et al, 2020; Krishnasamy et al, 2020; Kronborg et al, 2020; Kumar et al, 2020, 2021a, 2021b; Lagi et al, 2020; Lan et al, 2020; Lapostolle et al, 2020; …”
Section: Included Articlesmentioning
confidence: 99%